Art of the Book of Life - Gutierrez, Jorge R., (Dark Horse Comics, 2014)
A tale packed with adventure, The Book of Life celebrates the power of friendship and family, and the courage to follow your dreams. To determine whether the heart of humankind is pure and good, two godlike beings engage in an otherworldly wager during Mexico's annual Day of the Dead celebration. They tether two friends, Manolo and Joaquin, into vying for the heart of the beautiful and fiercely independent Maria, with comical and sometimes dangerous consequences. This volume is an inspirational behind-the-scenes look at the making of the animated feature film The Book of Life, from visionary producer Guillermo del Toro (Pan's Labyrinth) and director Jorge R. Gutierrez (El Tigre: The Adventures of Manny Rivera).